PEMANFAATAN WEBGIS UNTUK IDENTIFIKASI KESIAPAN FASILITAS KESEHATAN PADA WILAYAH BERPOTENSI BANJIR DI KABUPATEN MAGELANG - Mahasinul Akhlak, Muhammad Lutfi; Winanto, Andri; Nurhayati, Setia; Nuranisa, Angelita Nova (TRANSFORMASI, 2025)
Magelang Regency is one of the areas in Indonesia that has a high potential for flooding due to its geographical and hydrological conditions. This study aims to utilize WebGIS technology in identifying the readiness of health facilities in areas with potential for flooding in Magelang Regency. WebGIS results can display an administrative map of Magelang Regency, display a map of the distribution of health facilities, display a flood map and analysis of the identification of the readiness of health facilities in Magelang Regency. This website is expected to provide accurate and informative information as a basis for decision making in flood disaster mitigation planning. Based on the calculation of User Acceptance Testing (UAT), users produced a value of 88.8% of a total of 100%. Based on these results, users stated that they "strongly agree" with the system that was built that meets the user friendly criteria.